A porogen and its preparation method and application
By introducing porous inorganic materials and polyether segments into the water-soluble polyamide to form a porous agent with a block structure, the problem of agglomeration and coating of water-soluble polyamide during spinning is solved, and porous polyamide is realized The efficient preparation of fibers improves the mechanical and adsorption properties of fibers.
Patent Information
- Application Number
- CN202411428256.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing water-soluble polyamides are prone to agglomeration or coated by polyamide during spinning, resulting in the inability to form an effective pore structure and their crystallization ability is insufficient to be suitable for melt spinning processing.
Water-soluble polyamides with block structure consisting of polyamide segments and polyether segments are used, and porous inorganic materials are introduced as nucleating agents. Pore-generating agents are prepared through copolymerization reactions to ensure the crystallization ability and water-soluble of the polyamide segments. and evenly distributed in the fibers.
The uniform distribution of water-soluble polyamide and the formation of effective pore structure are achieved, the mechanical properties and adsorption properties of the fiber are improved, the agglomeration and coating problems during the spinning process are solved, and the water solubility and crystallization ability are improved.
Smart Images

Figure CN118932511B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-soluble polyamide and polyamide fiber, and specifically relates to a porogen and a preparation method and application thereof. Background Art
[0002] As one of the earliest synthetic fibers to achieve industrialization, polyamide fiber occupies an important position in the field of clothing fibers due to its excellent strength, abrasion resistance, elasticity, good moisture absorption and skin affinity. With the increase in the production of polyamide fibers and the growing market demand for fiber warmth and deodorization performance, it is particularly meaningful to combine porous structures with polyamide fibers to give them excellent warmth and adsorption properties. In addition, this porous structure will further broaden the application scope of polyamide fibers in adsorption, filtration and other fields.
[0003] Patent CN107287678A discloses a flame retardant and antistatic bio-based porous polyamide fiber composite material and its preparation method, using sebacic acid, itaconic acid, decanediamine and butanediamine as raw materials, ethanol as solvent, stirring at 50-60°C for 15min, cooling crystallization, suction filtration, washing and drying to obtain amide salt; under nitrogen protection, polyethylene glycol is added to dimethylacetamide, and then added to the amide salt, heated to melt reaction, after cooling, modified nano-silicon dioxide is added to mix, melt spinning, boiling and filtering with ethanol and water, glycerol soaking and vacuum drying to obtain a bio-based porous polyamide fiber membrane. Although the porous polyamide fiber prepared by the preparation method described in the patent has a porous structure, polyethylene glycol exists in the form of a blend, and it is easy to form droplets during the melt spinning process to produce hairy and broken fibers, so that the obtained fiber has low mechanical properties and cannot be used for clothing fibers.
[0004] In order to solve the above problems, it is necessary to find a new porogen that can replace polyethylene glycol.
[0005] Patent CN115232299A discloses a porogen masterbatch and its preparation method and application, wherein a porogen masterbatch coated with a water-soluble polyester and filled with micropores of a porous material is prepared, and the porogen masterbatch is cleverly used for melt blending and spinning with a thermoplastic fiber-grade polymer, and then the water-immersion treatment is performed to achieve the selective dissolution of the water-soluble polyester, and finally a fiber with a specific porous structure is prepared. Inspired by this, the present invention attempts to prepare a porogen coated with a water-soluble polyamide and filled with micropores of a porous material, melt blending and spinning the porogen and polyamide to obtain a fiber, and then the fiber is soaked in hot water and post-treated to obtain a porous polyamide fiber.
[0006] Patents US20100152328A1, US8541539B2 and US9087628B2 disclose a method for preparing a water-soluble polyamide, comprising caprolactam, ethylene glycol bis(2-aminoethyl) ether or ethylene glycol bis(3-aminopropyl) ether and sodium 5-sulfonate of isophthalic acid, at a copolymerization temperature of about 222-250°C and a copolymerization pressure of about 3 bar, and then maintaining a temperature of about 222-250°C at normal pressure for about 2-3 hours, and the solubility of the obtained water-soluble polyamide in water is about 10-70%. The document (Synthesis and characterization of a water-soluble nylon copolyamide. Polymer, 2013.) discloses a method for preparing a water-soluble copolyamide, comprising: salifying 5-sulfoisophthalic acid sodium and hexamethylenediamine in an anhydrous alcohol solution to obtain PA6SIP salt, salifying adipic acid and hexamethylenediamine in an anhydrous alcohol solution to obtain PA66 salt, then dissolving PA6SIP salt, PA66 salt and sodium hypophosphite in water, reacting at 180°C and 1.6MPa for 1.5h, raising the temperature by 50°C and gradually reducing the pressure to normal pressure, finally raising the reaction temperature to 270°C, evacuating to 40Pa, and reacting for 5h to obtain a water-soluble copolyamide.
[0007] However, the concept of the present invention cannot be realized by using the water-soluble polyamide of the prior art. On the one hand, although the existing water-soluble polyamide has excellent water solubility, it is usually in an amorphous state and has no crystallization ability. Even if the amount added is relatively small, it is easy to agglomerate during the drying process and the feeding process before spinning, and even cannot be fed. In the spinning process, there is even no time to cool down, which may cause droplets, filaments, broken fibers, etc., resulting in the inability to spin. On the other hand, in the melt blending spinning process, since the water-soluble polyamide is added in a small proportion, it is easily coated by the polyamide. This will result in the water-soluble polyamide coated by the polyamide being difficult to contact water and dissolve in water during the hydrothermal treatment, making it difficult to form an effective pore structure.
[0008] Therefore, it is necessary to prepare a porogen which is coated with a new water-soluble polyamide and fills the micropores of a porous material, so as to obtain a porous polyamide fiber. Summary of the invention
[0009] The purpose of the present invention is to solve the problems existing in the prior art and provide a porogen and a preparation method and application thereof.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] A porogen includes a porous inorganic material and a water-soluble polyamide that coats and fills the porous inorganic material. The structural formula of the water-soluble polyamide is as follows:
[0012] ;
[0013] In the formula, m is an integer in the range of [6, 28], n is an integer in the range of [1, 5], x is an integer in the range of [4, 20], y is an integer in the range of [2, 18], and R is a polyoxyethylene segment or a polyoxypropylene segment.
[0014] The present invention newly synthesizes a new water-soluble polyamide, and prepares it together with a porous inorganic material into a porogen in the melt spinning process. Since the water-soluble polyamide is a block structure formed by a polyamide segment and a polyether segment, and the porous inorganic material is also introduced as a nucleating agent, the crystallization ability of the polyamide segment is guaranteed, making it suitable for melt spinning processing; since the present invention introduces a sulfonate group into the polyamide segment, its good water solubility ensures that the polyamide segment can be dissolved in water, which can avoid water stagnation caused by the crystallization of the polyamide segment. The solubility performance is weakened; since the polyether segment is in an amorphous state, water molecules can quickly enter the polymer, further improving the water solubility of the water-soluble polyamide; since the water-soluble polyamide is composed of polyamide segments and polyether segments, the presence of the polyamide segments enables the water-soluble polyamide to have good compatibility with the polyamide, ensuring the uniform distribution of the water-soluble polyamide in the fiber, while there is incompatibility between the polyether segment and the polyamide, forming a phase separation structure with the polyamide, avoiding the water-soluble polyamide being completely coated by the polyamide.
[0015] As the preferred technical solution:
[0016] In the porogen as described above, the porous inorganic material is a porous carbon material or a porous natural mineral powder, the particle size is 0.5 to 5 microns, and the pore size does not exceed 200 nanometers.
[0017] The porogen as described above has a relative molecular mass of 14000-33000 g / mol, a molecular weight distribution index of 1.5-3.0, a melting point of 170-220° C., a crystallization temperature of 120-180° C., and a solubility of the porogen in hot water at 50-100° C. of 10-50 g / 100 g.
[0018] The present invention also provides a method for preparing a porogen as described in any of the above items, wherein caprolactam, a dibasic acid, an amide salt and deionized water are mixed and subjected to a ring-opening reaction to obtain a double-terminal carboxyl polyamide prepolymer, and then a polyether diamine, a reaction aid and a porous inorganic material are added to carry out a condensation reaction to obtain the porogen, wherein the amide salt is obtained by a salt-forming reaction of sodium 5-sulfonate of isophthalic acid and an aliphatic diamine.
[0019] As the preferred technical solution:
[0020] In the method as described above, the dibasic acid is one or more dibasic acids of C4 to C20;
[0021] The relative molecular mass of the double-terminated carboxyl prepolymer is 1500g / mol~5000g / mol;
[0022] The polyether diamine is one or more of polyoxyethylene diamine and polyoxypropylene diamine; the relative molecular mass of the polyether diamine is 400-4000 g / mol;
[0023] The reaction aid is a mixture of a catalyst (e.g., hypophosphorous acid, N-acetyl caprolactam or sodium hypophosphite), an antioxidant (e.g., one or more of antioxidant 1010, antioxidant 168 or antioxidant 616) and a heat stabilizer (e.g., one or more of triphenyl phosphite and trimethyl phosphate);
[0024] The aliphatic diamine is one or more of C4 to C20 diamines.
[0025] According to the method described above, the molar ratio of caprolactam to the dibasic acid is 6-28:1, the mass of the amide salt is 50-100% of the mass of caprolactam, the mass of deionized water is 2-3% of the mass of caprolactam, the molar ratio of the polyether diamine to the dibasic acid is 1-1.05:1, the mass of the catalyst is 0.01-1wt% of the total mass of the caprolactam, the dibasic acid, the amide salt and the polyether diamine, the mass of the antioxidant is 100-500ppm of the total mass of the caprolactam, the dibasic acid, the amide salt and the polyether diamine, the mass of the heat stabilizer is 100-500ppm of the total mass of the caprolactam, the dibasic acid, the amide salt and the polyether diamine, and the mass of the porous inorganic material is not less than 5% of the total mass of the caprolactam, the dibasic acid, the amide salt and the polyether diamine.
[0026] In the method described above, the pressure of the ring-opening reaction is 0.01~0.6MPa, the temperature is 210~250℃, and the time is 2~5h; the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction, the pressure of the pre-polycondensation reaction is 0.01~0.3MPa, the temperature is 230~260℃, and the time is 1~3h, and the pressure of the final polycondensation reaction is 5~300Pa, the temperature is 250~280℃, and the time is 3~5h.
[0027] According to the method described above, the preparation process of the amide salt is as follows: sodium 5-sulfoisophthalic acid, aliphatic diamine, and deionized water are placed in a salt-forming reactor for reaction until the pH value of the system is in the range of 7.2 to 7.5, wherein the molar ratio of sodium 5-sulfoisophthalic acid and aliphatic diamine is 1:1.01 to 1.05, and the amount of deionized water is 50 to 80 wt % based on the total mass of sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water; the reaction temperature is 50 to 95 ° C, the reaction pressure is 0.1 to 0.2 MPa, and the reaction is accompanied by stirring at a stirring speed of 100 to 200 r / min.
[0028] The present invention also provides a use of a porogen as described in any one of the above items, wherein the porogen and polyamide are melt-blended and spun to obtain fibers, and then the fibers are soaked in hot water and post-treated to obtain porous polyamide fibers.
[0029] As the preferred technical solution:
[0030] In the above application, the polyamide is fiber grade polyamide 6, fiber grade polyamide 66 or fiber grade polyamide 6 / 66;
[0031] The mass of the porogen accounts for 5-30% of the total mass of the porogen and the polyamide;
[0032] Melt blend spinning adopts UDY process, POY process or FDY process;
[0033] The spinning process parameters of the UDY process include: spinning temperature 220~280℃, spinning speed 500~1500m / min, cooling air temperature 20~30℃, cooling air speed 0.3~1m / s, cooling air relative humidity 60%~80%;
[0034] The spinning process parameters of the POY process include: spinning temperature 220~280℃, spinning speed 1500~2500m / min, cooling air temperature 15~25℃, cooling air speed 0.3~0.6m / s, cooling air relative humidity 60%~80%;
[0035] The spinning process parameters of the FDY process include: spinning temperature 220~280℃, spinning speed 2500~3500m / min, cooling air temperature 15~20℃, cooling air speed 0.3~0.6m / s, cooling air relative humidity 70%~85%;
[0036] The soaking temperature is 50~100℃, the soaking time is 0.5~2h; the mass ratio of fiber to hot water is 1:10~60;
[0037] The single fiber fineness of porous polyamide fiber is 1.1~5.5dtex, the breaking strength is 1.5~3.0cN / dtex, and the breaking elongation is 10~50%; the pore size of the porous structure in the porous polyamide fiber is 10~300nm; the specific surface area of the porous polyamide fiber is 2~20m 2 / g, the specific surface area of the fiber increases by 2~12.5 times compared with that before hydrothermal treatment, and the weight decreases by 5~30%.
[0038] The principle of the present invention is as follows:
[0039] The present invention prepares a water-soluble polyamide through copolymerization reaction. The water-soluble polyamide has the characteristics of crystallization ability and water solubility, can be dissolved in water at a certain temperature, and its good water solubility is achieved by the joint action of the hydrophilic polyether segment and the sodium sulfonate group in the molecular chain. The hydrophilic polyether segment exists in the polymer in an amorphous form. Since water first enters the polymer system from the amorphous region, the introduction of the polyether segment can promote the entry of water molecules into the polymer system; the introduction of sodium 5-sulfonate of isophthalic acid destroys the regularity of the polyamide segment to a certain extent, and the presence of the sulfonate group can quickly capture the water molecules entering the polymer system, thereby further destroying the hydrogen bond structure between the polyamide molecular chains, and finally dissolving the polyamide molecular chains in water, and the whole dissolution process presents a phenomenon of swelling first and then dissolving. In addition, in order to compensate for the problem of decreased crystallization ability caused by sodium 5-sulfonisophthalic acid and ensure that the crystallization performance of the polyamide chain segment is suitable for melt spinning processing, porous inorganic materials are introduced into the water-soluble polyamide polymerization system by in-situ polymerization. This not only avoids the agglomeration of the porous inorganic materials in the polymer system, but also allows the porous inorganic materials to be used as nucleating agents to promote the crystallization of the polyamide chain segments.
[0040] After the water-soluble polyamide is blended and spun with polyamide, since the water-soluble polyamide is composed of polyamide segments and polyether segments, the presence of the polyamide segments enables the water-soluble polyamide to have good compatibility with the polyamide, ensuring the uniform distribution of the water-soluble polyamide in the fiber, while the polyether segments are incompatible with the polyamide, forming a phase separation structure with the polyamide, avoiding the water-soluble polyamide from being completely coated by the polyamide. On this basis, the blended fiber is subjected to hydrothermal treatment, and the water-soluble polyamide filled in the pores of the porous inorganic material and coated on the outer surface of the porous material in the fiber will be dissolved, and the water-soluble polyamide dispersed in the polyamide will also be dissolved to form a pore structure, and the polyamide serves as the skeleton of the fiber and provides mechanical strength, and the porous inorganic material is well dispersed in the matrix to provide excellent adsorption performance.
[0041] Beneficial effects:
[0042] (1) In the present invention, the polyether chain segment in the water-soluble polyamide molecular chain and sodium 5-sulfoisophthalic acid make the polyamide molecular chain have good water solubility. The whole dissolution process shows that it first swells and then dissolves. The porous inorganic material is introduced as a nucleating agent to promote the crystallization ability of the polyamide chain segment, thereby solving the problem of decreased crystallization ability due to the introduction of sodium 5-sulfoisophthalic acid, and ensuring the smooth progress of melt blending spinning.
[0043] (2) In the present invention, the water-soluble polyamide has a block structure consisting of a polyamide segment and a polyether segment. The presence of the polyamide segment enables good compatibility between the water-soluble polyamide and the polyamide, thereby ensuring uniform distribution of the water-soluble polyamide in the fiber. At the same time, the incompatibility between the polyether segment and the polyamide prevents the water-soluble polyamide from being completely covered by the polyamide during the spinning process, thereby obtaining a more uniform pore structure during the hydrothermal treatment process.
[0044] (3) In the present invention, the porous inorganic material is introduced into the water-soluble polyamide system by in-situ polymerization, thereby improving the dispersibility of the porous material in the polymer system. The water-soluble polyamide, as a carrier of the porous material, can be coated on the surface of the porous material and filled in the pores of the porous material, thereby avoiding the problem caused by the pores of the porous material being filled with polyamide during the melt spinning process. The water-soluble polyamide can be dissolved by water during the hydrothermal treatment process, thereby releasing the pore structure of the porous inorganic material.
[0045] (4) The porogen and preparation method thereof of the present invention have simple process, high production efficiency and low cost, and can be prepared on a large scale in an existing polymerization device. The addition amount of the prepared porogen can be flexibly adjusted according to the application requirements of the fiber. The obtained porous polyamide fiber has excellent adsorption and warmth retention functions, and can be widely used in adsorption materials, filter materials, clothing fibers, medical materials and other fields, and has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 It is a DSC curve diagram of the porogen of Example 5 in the present invention. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0048] The structural formula of the water-soluble polyamide in the following embodiments is as follows:
[0049] ;
[0050] In the formula, m is an integer in the range of [6, 28], n is an integer in the range of [1, 5], x is an integer in the range of [4, 20], y is an integer in the range of [2, 18], and R is a polyoxyethylene segment or a polyoxypropylene segment.
[0051] Testing methods for relevant performance indicators:
[0052] The relative molecular mass of the double-terminated carboxyl polyamide prepolymer was tested by GPC. The instrument was an Agilent 1260 gel chromatograph, the chromatographic column was an Agilent HFIP series, the mobile phase was hexafluoroisopropanol, some sodium trifluoroacetate was added, the concentration of sodium trifluoroacetate was 0.02 mol / L, and the test temperature was 40°C.
[0053] The relative molecular mass and molecular weight distribution index of the porogen were tested by GPC. The instrument was Agilent 1260 gel chromatograph, the chromatographic column was Agilent HFIP series, the mobile phase was hexafluoroisopropanol, some sodium trifluoroacetate was added, the concentration of sodium trifluoroacetate was 0.02 mol / L, and the test temperature was 40°C.
[0054] Melting point and crystallization temperature of porogen: Tested in accordance with GB / T 19466.3-2004 Plastics Differential Scanning Calorimetry (DSC) Part 3: Determination of Melting and Crystallization Temperature and Thermal Enthalpy;
[0055] The breaking strength and breaking elongation of porous polyamide fiber are tested in accordance with GB / T 14344-2008 Test method for tensile properties of chemical fiber filaments.
[0056] Specific surface area of porous polyamide fiber: The specific surface area of the fiber was measured using an Autosorb-iQ fully automatic rapid specific surface and porosity analyzer.
[0057] Example 1
[0058] A method for preparing a porogen, the specific steps are as follows:
[0059] (1) Raw material preparation:
[0060] Porous inorganic materials: sepiolite powder (Luonan County Qinxing Sepiolite Development Co., Ltd.), with an average particle size of 3 microns and an average pore size of 100 nanometers;
[0061] Caprolactam;
[0062] Sodium 5-sulfoisophthalate;
[0063] Dibasic acid: adipic acid;
[0064] Aliphatic diamine: 1,20-eicosanediamine, CAS: 34540-46-0;
[0065] Polyether diamine: polyoxyethylene diamine, relative molecular mass is 1000g / mol;
[0066] Reaction aid: a mixture of catalyst (N-acetyl caprolactam), antioxidant (antioxidant 1010) and heat stabilizer (triphenyl phosphite);
[0067] Deionized water;
[0068] (2) Preparation of amide salt:
[0069] Sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water are placed in a salt-forming reactor for reaction until the pH value of the system is in the range of 7.2 to 7.5, wherein the molar ratio of sodium 5-sulfoisophthalic acid and aliphatic diamine is 1:1.01, and the amount of deionized water is 50wt% based on the total mass of sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water; the reaction temperature is 95°C, the reaction pressure is 0.1MPa, and the reaction is accompanied by stirring at a stirring speed of 150r / min;
[0070] (3) Preparation of porogen:
[0071] After mixing caprolactam, dibasic acid, amide salt and deionized water, a ring-opening reaction is carried out at a pressure of 0.6 MPa and a temperature of 250°C for 2 hours to obtain a double-terminal carboxyl polyamide prepolymer with a relative molecular mass of 4000 g / mol, and then a polyether diamine, a reaction aid and a porous inorganic material are added to carry out a polycondensation reaction to obtain a porogen, wherein the polycondensation reaction includes two stages: a pre-polycondensation reaction and a final polycondensation reaction. The pre-polycondensation reaction is carried out at a pressure of 0.2 MPa, a temperature of 250°C and a time of 1 hour, and the final polycondensation reaction is carried out at a pressure of 5 Pa, a temperature of 260°C and a time of 3 hours;
[0072] During the reaction, the molar ratio of caprolactam to the dibasic acid is 23:1, the mass of the amide salt is 50% of the mass of caprolactam, the mass of deionized water is 2% of the mass of caprolactam, the molar ratio of the polyether diamine to the dibasic acid is 1:1, the mass of the catalyst is 0.01wt% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the antioxidant is 100ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the heat stabilizer is 350ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, and the mass of the porous inorganic material is 5% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine.
[0073] The final porogen is composed of a porous inorganic material and a water-soluble polyamide that coats and fills the porous inorganic material. In the structural formula of the water-soluble polyamide, m is 23, n is 2, x is 20, y is 4, and R is a polyoxyethylene segment. The relative molecular mass of the porogen is 21000 g / mol, the molecular weight distribution index is 1.8, the melting point is 210°C, the crystallization temperature is 170°C, and the solubility of the porogen in hot water at 60°C is 35g / 100g.
[0074] Comparative Example 1
[0075] A method for preparing a porogen is basically the same as that of Example 1, except that there is no porous inorganic material in step (1) and step (3) of this comparative example.
[0076] The final porogen is composed of water-soluble polyamide, and has a relative molecular mass of 21000 g / mol, a molecular weight distribution index of 1.8, a melting point of 210°C, a crystallization temperature of 110°C, and a solubility of the porogen in hot water at 60°C of 35 g / 100 g.
[0077] Compared with Example 1, the crystallization temperature of the porogen prepared in Comparative Example 1 is significantly lower than that in Example 1. This is because the porous inorganic material can act as a nucleating agent in the polymer system, which can promote the crystallization of the polymer and thus increase the crystallization temperature. No nucleating agent is added in Comparative Example 1, so the crystallization temperature is significantly lower than that of Example 1. Too low a crystallization temperature will cause bonding, droplets, broken wires and other phenomena that affect the processing process during the subsequent fiber forming process.
[0078] Comparative Example 2
[0079] A method for preparing a porogen is basically the same as that in Example 1, except that isophthalic acid is used in this comparative example to replace sodium 5-sulfonate of isophthalic acid in Example 1.
[0080] The final porogen is composed of a porous inorganic material and a polyamide coated and filled with the porous inorganic material. The relative molecular mass of the porogen is 21000 g / mol, the molecular weight distribution index is 1.8, the melting point is 210°C, the crystallization temperature is 170°C, and the solubility of the porogen in hot water at 60°C is 1g / 100g.
[0081] Compared with Example 1, the solubility of the porogen prepared in Comparative Example 2 in hot water is significantly worse. This is because there is no hydrophilic group on isophthalic acid, and the polyamide segment will promote crystallization under the action of the inorganic porous material as a nucleating agent. Although water molecules can easily enter the amorphous region of the polymer, the lack of hydrophilic groups in the polyamide crystal region makes it difficult for water molecules to enter the crystal region to dissolve the molecular chain. The presence of the sulfonate group in the sodium 5-sulfonate isophthalic acid in Example 1 can quickly capture the water molecules entering the polymer system, thereby further destroying the hydrogen bond structure between the polyamide molecular chains, and finally dissolving the polyamide molecular chains in water. Therefore, the solubility of the porogen in Comparative Example 2 in hot water is significantly worse than that in Example 1.
[0082] Comparative Example 3
[0083] A method for preparing a porogen is basically the same as that in Example 1, except that: in step (1) of this comparative example, no polyether diamine is prepared, and in step (3), no polyether diamine is added after the ring-opening reaction.
[0084] The final porogen is composed of a porous inorganic material and a water-soluble polyamide that coats and fills the porous inorganic material. The relative molecular mass of the porogen is 4000 g / mol, the molecular weight distribution index is 3.1, the melting point is 210°C, the crystallization temperature is 180°C, and the solubility of the porogen in hot water at 60°C is 25g / 100g.
[0085] Compared with Example 1, the relative molecular mass of the porogen prepared in Comparative Example 3 is significantly reduced, and the solubility in hot water is slightly decreased. This is because if the polyether diamine is not added during the polymerization process, the subsequent polycondensation step will not be able to achieve the growth of the molecular chain. Therefore, the relative molecular mass of the porogen in Comparative Example 3 is consistent with the molecular weight of the double-terminal carboxyl polyamide prepolymer in Example 1. The too low molecular weight makes the polymer of Comparative Example 3 unable to be applied to the subsequent processing process; at the same time, due to the lack of polyether soft segments, the speed at which water molecules enter the polymer system is significantly slowed down, and due to the increase in crystallinity, the dissolution of the polyamide segments in water becomes difficult. Therefore, the solubility of the porogen in Comparative Example 3 in hot water is slightly lower than that of Example 1.
[0086] Example 2
[0087] A method for preparing a porogen, the specific steps are as follows:
[0088] (1) Raw material preparation:
[0089] Porous inorganic materials: graphene micro-nano powder (Jiangxi Zhushengfu Nanotechnology Co., Ltd.), with an average particle size of 0.5 μm and an average pore size of 100 nm;
[0090] Caprolactam;
[0091] Sodium 5-sulfoisophthalate;
[0092] Dibasic acid: sebacic acid;
[0093] Aliphatic diamine: diaminobutane;
[0094] Polyether diamine: polyoxypropylene diamine, relative molecular mass is 2000g / mol;
[0095] Reaction aid: a mixture of catalyst (sodium hypophosphite), antioxidant (antioxidant 1010) and heat stabilizer (triphenyl phosphite);
[0096] Deionized water;
[0097] (2) Preparation of amide salt:
[0098] Sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water are placed in a salt-forming reactor to react until the pH value of the system is in the range of 7.2 to 7.5, wherein the molar ratio of sodium 5-sulfoisophthalic acid to aliphatic diamine is 1:1.05, and the amount of deionized water is 80wt% based on the total mass of sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water; the reaction temperature is 50°C, the reaction pressure is 0.1MPa, and the reaction is accompanied by stirring at a stirring speed of 200r / min;
[0099] (3) Preparation of porogen:
[0100] After mixing caprolactam, dibasic acid, amide salt and deionized water, a ring-opening reaction is carried out at a pressure of 0.5 MPa and a temperature of 230°C for 4 hours to obtain a double-terminal carboxyl polyamide prepolymer with a relative molecular mass of 3000 g / mol, and then a polyether diamine, a reaction aid and a porous inorganic material are added to carry out a polycondensation reaction to obtain a porogen, wherein the polycondensation reaction includes two stages: a pre-polycondensation reaction and a final polycondensation reaction. The pre-polycondensation reaction is carried out at a pressure of 0.1 MPa, a temperature of 230°C and a time of 2 hours, and the final polycondensation reaction is carried out at a pressure of 100 Pa, a temperature of 265°C and a time of 4 hours;
[0101] During the reaction, the molar ratio of caprolactam to the dibasic acid is 16:1, the mass of the amide salt is 50% of the mass of caprolactam, the mass of deionized water is 2.5% of the mass of caprolactam, the molar ratio of the polyether diamine to the dibasic acid is 1.03:1, the mass of the catalyst is 0.1wt% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the antioxidant is 130ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the heat stabilizer is 400ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, and the mass of the porous inorganic material is 7% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine.
[0102] The final porogen is composed of a porous inorganic material and a water-soluble polyamide that coats and fills the porous inorganic material. In the structural formula of the water-soluble polyamide, m is 16, n is 3, x is 4, y is 8, and R is a polyoxypropylene segment. The relative molecular mass of the porogen is 25,000 g / mol, the molecular weight distribution index is 1.6, the melting point is 200°C, the crystallization temperature is 175°C, and the solubility of the porogen in hot water at 50°C is 40g / 100g.
[0103] Example 3
[0104] A method for preparing a porogen, the specific steps are as follows:
[0105] (1) Raw material preparation:
[0106] Porous inorganic materials: high-temperature bamboo charcoal powder (Jiangxi Zhushengfu Nanotechnology Co., Ltd.), with an average particle size of 4 μm and an average pore size of 200 nm;
[0107] Caprolactam;
[0108] Sodium 5-sulfoisophthalate;
[0109] Dibasic acid: succinic acid;
[0110] Aliphatic diamine: dodecanediamine;
[0111] Polyether diamine: a mixture of polyoxyethylene diamine and polyoxypropylene diamine in a mass ratio of 1:1, wherein the relative molecular weights of the polyoxyethylene diamine and the polyoxypropylene diamine are both 4000 g / mol;
[0112] Reaction aid: a mixture of catalyst (sodium hypophosphite), antioxidant (antioxidant 1010) and heat stabilizer (triphenyl phosphite);
[0113] Deionized water;
[0114] (2) Preparation of amide salt:
[0115] Sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water are placed in a salt-forming reactor to react until the pH value of the system is in the range of 7.2 to 7.5, wherein the molar ratio of sodium 5-sulfoisophthalic acid to aliphatic diamine is 1:1.03, and the amount of deionized water is 60wt% based on the total mass of sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water; the reaction temperature is 50°C, the reaction pressure is 0.1MPa, and the reaction is accompanied by stirring at a stirring speed of 100r / min;
[0116] (3) Preparation of porogen:
[0117] After mixing caprolactam, dibasic acid, amide salt and deionized water, a ring-opening reaction is carried out at a pressure of 0.01 MPa and a temperature of 210°C for 3 hours to obtain a double-terminal carboxyl polyamide prepolymer with a relative molecular mass of 1500 g / mol, and then a polyether diamine, a reaction aid and a porous inorganic material are added to carry out a polycondensation reaction to obtain a porogen, wherein the polycondensation reaction includes two stages: a pre-polycondensation reaction and a final polycondensation reaction. The pre-polycondensation reaction is carried out at a pressure of 0.01 MPa, a temperature of 210°C and a time of 1 hour, and the final polycondensation reaction is carried out at a pressure of 50 Pa, a temperature of 250°C and a time of 4 hours;
[0118] During the reaction, the molar ratio of caprolactam to the dibasic acid is 6:1, the mass of the amide salt is 100% of the mass of caprolactam, the mass of deionized water is 2.2% of the mass of caprolactam, the molar ratio of the polyether diamine to the dibasic acid is 1.02:1, the mass of the catalyst is 1wt% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the antioxidant is 260ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the heat stabilizer is 200ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, and the mass of the porous inorganic material is 10% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine.
[0119] The final porogen is composed of a porous inorganic material and a water-soluble polyamide that coats and fills the porous inorganic material. In the structural formula of the water-soluble polyamide, m is 6, n is 1, x is 12, y is 2, one part R is a polyoxyethylene segment, and the other part R is a polyoxypropylene segment. The mass ratio of the polyoxyethylene segment to the polyoxypropylene segment is 1:1. The relative molecular mass of the porogen is 14000 g / mol, the molecular weight distribution index is 3, the melting point is 170°C, the crystallization temperature is 120°C, and the solubility of the porogen in hot water at 80°C is 50g / 100g.
[0120] Example 4
[0121] A method for preparing a porogen, the specific steps are as follows:
[0122] (1) Raw material preparation:
[0123] Porous inorganic material: diatomaceous earth (Linjiang Changbaishan Filter Aid Co., Ltd.), with an average particle size of 2 μm and an average pore size of 50 nm;
[0124] Caprolactam;
[0125] Sodium 5-sulfoisophthalate;
[0126] Dibasic acid: eicosanedioic acid;
[0127] Aliphatic diamine: hexamethylenediamine;
[0128] Polyether diamine: polyoxyethylene diamine, relative molecular mass is 3000g / mol;
[0129] Reaction aid: a mixture of catalyst (sodium hypophosphite), antioxidant (antioxidant 168) and heat stabilizer (trimethyl phosphate);
[0130] Deionized water;
[0131] (2) Preparation of amide salt:
[0132] Sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water are placed in a salt-forming reactor for reaction until the pH value of the system is in the range of 7.2 to 7.5, wherein the molar ratio of sodium 5-sulfoisophthalic acid to aliphatic diamine is 1:1.05, and the amount of deionized water is 50wt% based on the total mass of sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water; the reaction temperature is 60°C, the reaction pressure is 0.2MPa, and the reaction is accompanied by stirring at a stirring speed of 180r / min;
[0133] (3) Preparation of porogen:
[0134] After mixing caprolactam, dibasic acid, amide salt and deionized water, a ring-opening reaction is carried out at a pressure of 0.3 MPa and a temperature of 220°C for 5 hours to obtain a double-terminal carboxyl polyamide prepolymer with a relative molecular mass of 2000 g / mol, and then a polyether diamine, a reaction aid and a porous inorganic material are added to carry out a polycondensation reaction to obtain a porogen, wherein the polycondensation reaction includes two stages: a pre-polycondensation reaction and a final polycondensation reaction. The pre-polycondensation reaction is carried out at a pressure of 0.15 MPa, a temperature of 220°C and a time of 2 hours, and the final polycondensation reaction is carried out at a pressure of 200 Pa, a temperature of 280°C and a time of 4 hours;
[0135] During the reaction, the molar ratio of caprolactam to the dibasic acid is 9:1, the mass of the amide salt is 60% of the mass of caprolactam, the mass of deionized water is 3% of the mass of caprolactam, the molar ratio of the polyether diamine to the dibasic acid is 1.04:1, the mass of the catalyst is 0.9wt% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the antioxidant is 500ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the heat stabilizer is 100ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, and the mass of the porous inorganic material is 5% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine.
[0136] The final porogen is composed of a porous inorganic material and a water-soluble polyamide that coats and fills the porous inorganic material. In the structural formula of the water-soluble polyamide, m is 9, n is 2, x is 6, y is 18, and R is a polyoxyethylene segment. The relative molecular mass of the porogen is 18000 g / mol, the molecular weight distribution index is 1.5, the melting point is 180°C, the crystallization temperature is 150°C, and the solubility of the porogen in hot water at 70°C is 45g / 100g.
[0137] Example 5
[0138] A method for preparing a porogen, the specific steps are as follows:
[0139] (1) Raw material preparation:
[0140] Porous inorganic material: diatomaceous earth (Changbaishan Filter Aid Co., Ltd., Linjiang City), with an average particle size of 2 μm and an average pore size of 100 nm;
[0141] Caprolactam;
[0142] Sodium 5-sulfoisophthalate;
[0143] Dibasic acid: adipic acid;
[0144] Aliphatic diamine: decanediamine;
[0145] Polyether diamine: polyoxyethylene diamine, relative molecular mass is 400g / mol;
[0146] Reaction aid: a mixture of catalyst (sodium hypophosphite), antioxidant (antioxidant 616) and heat stabilizer (triphenyl phosphite);
[0147] Deionized water;
[0148] (2) Preparation of amide salt:
[0149] Sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water are placed in a salt-forming reactor to react until the pH value of the system is in the range of 7.2-7.5, wherein the molar ratio of sodium 5-sulfoisophthalic acid and aliphatic diamine is 1:1.01, and the amount of deionized water is 70wt% based on the total mass of sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water; the reaction temperature is 80°C, the reaction pressure is 0.15MPa, and the reaction is accompanied by stirring at a stirring speed of 200r / min;
[0150] (3) Preparation of porogen:
[0151] After mixing caprolactam, dibasic acid, amide salt and deionized water, a ring-opening reaction is carried out at a pressure of 0.6 MPa and a temperature of 230°C for 3 hours to obtain a double-terminal carboxyl polyamide prepolymer with a relative molecular mass of 2000 g / mol, and then a polyether diamine, a reaction aid and a porous inorganic material are added to carry out a polycondensation reaction to obtain a porogen, wherein the polycondensation reaction includes two stages: a pre-polycondensation reaction and a final polycondensation reaction. The pre-polycondensation reaction is carried out at a pressure of 0.3 MPa, a temperature of 260°C and a time of 3 hours, and the final polycondensation reaction is carried out at a pressure of 300 Pa, a temperature of 255°C and a time of 4 hours;
[0152] During the reaction, the molar ratio of caprolactam to the dibasic acid is 9:1, the mass of the amide salt is 80% of the mass of caprolactam, the mass of deionized water is 3% of the mass of caprolactam, the molar ratio of the polyether diamine to the dibasic acid is 1.05:1, the mass of the catalyst is 0.6wt% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the antioxidant is 350ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the heat stabilizer is 200ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, and the mass of the porous inorganic material is 5% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine.
[0153] The final porogen is composed of a porous inorganic material and a water-soluble polyamide that coats and fills the porous inorganic material. In the structural formula of the water-soluble polyamide, m is 9, n is 2, x is 10, y is 4, and R is a polyoxyethylene segment. The relative molecular mass of the porogen is 33000 g / mol, the molecular weight distribution index is 2.8, and the DSC curve is as follows: Figure 1 As shown, the melting point is 180°C, the crystallization temperature is 140°C, and the solubility of the porogen in hot water at 100°C is 10g / 100g.
[0154] Example 6
[0155] A method for preparing a porogen, the specific steps are as follows:
[0156] (1) Raw material preparation:
[0157] Porous inorganic materials: high-temperature bamboo charcoal powder (Jiangxi Zhushengfu Nanotechnology Co., Ltd.), with an average particle size of 5 μm and an average pore size of 150 nm;
[0158] Caprolactam;
[0159] Sodium 5-sulfoisophthalate;
[0160] Dicarboxylic acid: dodecanedioic acid;
[0161] Aliphatic diamine: hexamethylenediamine;
[0162] Polyether diamine: polyoxypropylene diamine, relative molecular mass is 800g / mol;
[0163] Reaction aid: a mixture of catalyst (hypophosphorous acid), antioxidant (antioxidant 1010) and heat stabilizer (trimethyl phosphate);
[0164] Deionized water;
[0165] (2) Preparation of amide salt:
[0166] Sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water are placed in a salt-forming reactor to react until the pH value of the system is in the range of 7.2 to 7.5, wherein the molar ratio of sodium 5-sulfoisophthalic acid to aliphatic diamine is 1:1.04, and the amount of deionized water is 50wt% based on the total mass of sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water; the reaction temperature is 70°C, the reaction pressure is 0.15MPa, and the reaction is accompanied by stirring at a stirring speed of 200r / min;
[0167] (3) Preparation of porogen:
[0168] After mixing caprolactam, dibasic acid, amide salt and deionized water, a ring-opening reaction is carried out at a pressure of 0.4 MPa and a temperature of 240°C for 3 hours to obtain a double-terminal carboxyl polyamide prepolymer with a relative molecular mass of 5000 g / mol, and then a polyether diamine, a reaction aid and a porous inorganic material are added to carry out a polycondensation reaction to obtain a porogen, wherein the polycondensation reaction includes two stages: a pre-polycondensation reaction and a final polycondensation reaction. The pre-polycondensation reaction is carried out at a pressure of 0.25 MPa, a temperature of 240°C and a time of 2 hours, and the final polycondensation reaction is carried out at a pressure of 100 Pa, a temperature of 260°C and a time of 5 hours;
[0169] During the reaction, the molar ratio of caprolactam to the dibasic acid is 28:1, the mass of the amide salt is 50% of the mass of caprolactam, the mass of deionized water is 2% of the mass of caprolactam, the molar ratio of the polyether diamine to the dibasic acid is 1.03:1, the mass of the catalyst is 0.5wt% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the antioxidant is 200ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, the mass of the heat stabilizer is 500ppm of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine, and the mass of the porous inorganic material is 8% of the total mass of caprolactam, dibasic acid, amide salt and polyether diamine.
[0170] The final porogen is composed of a porous inorganic material and a water-soluble polyamide that coats and fills the porous inorganic material. In the structural formula of the water-soluble polyamide, m is 28, n is 5, x is 6, y is 10, and R is a polyoxypropylene segment. The relative molecular mass of the porogen is 30,000 g / mol, the molecular weight distribution index is 2.1, the melting point is 220°C, the crystallization temperature is 180°C, and the solubility of the porogen in hot water at 90°C is 30g / 100g.
[0171] Example 7
[0172] A method for preparing porous polyamide fiber, the specific steps are as follows:
[0173] (1) Raw material preparation:
[0174] Porogen: prepared in Example 1 above;
[0175] Polyamide: fiber grade polyamide 6;
[0176] (2) Preparation of porous polyamide fibers:
[0177] After melt blending and spinning the porogen and polyamide by FDY process to obtain fibers, the fibers are soaked in hot water and post-treated to obtain porous polyamide fibers;
[0178] Among them, the mass of the porogen accounts for 5% of the total mass of the porogen and polyamide, the spinning temperature is 250°C, the spinning speed is 3000m / min, the cooling air temperature is 20°C, the cooling air speed is 0.3m / s, the cooling air relative humidity is 75%, the immersion temperature is 65°C, and the time is 1h; the mass of fiber and hot water is 1:35.
[0179] The final porous polyamide fiber has a single fiber fineness of 2 dtex, a breaking strength of 2.9 cN / dtex, and a breaking elongation of 28%. The average pore size of the porous structure in the porous polyamide fiber is 193 nm, and the specific surface area of the porous polyamide fiber is 13 m 2 / g, the comparative area of the fiber increased by 7.6 times and the weight decreased by 15% compared with that before hydrothermal treatment.
[0180] Comparative Example 4
[0181] A method for preparing porous polyamide fiber is basically the same as Example 7, except that the porogen in this comparative example is obtained by blending a water-soluble polyamide of the prior art (Synthesis and characterization of a water-soluble nyloncopolyamide. Polymer, 2013.) and a porous inorganic material (sepiolite powder) in a mass ratio of 95:5.
[0182] The final porous polyamide fiber has a single fiber fineness of 3.2 dtex, a breaking strength of 1.9 cN / dtex, and a breaking elongation of 32%. The average pore size of the porous structure in the porous polyamide fiber is 305 nm. The specific surface area of the porous polyamide fiber is 1.65 m 2 / g, the comparative area of the fiber increased by 0.3 times and the mass decreased by 1.1% compared with that before hydrothermal treatment.
[0183] Compared with Example 7, the porous polyamide fiber prepared in Comparative Example 4 has a larger single-filament fineness and a decreased mechanical strength, and the specific surface area of the porous polyamide fiber before the hot water treatment increases and the weight reduction is not obvious. This is because the porogen in Comparative Example 4 is obtained by blending the water-soluble polyamide with the porous inorganic material after the preparation, which makes the dispersion of the porous inorganic material in the matrix poor and the porous inorganic material is prone to agglomeration. Therefore, the fiber is subjected to uneven force during the stretching process, which is prone to stress concentration, resulting in a decrease in the spinnability and breaking strength of the fiber; at the same time, the water-soluble polyamide in Comparative Example 4 has excellent compatibility with the spinning-grade polyamide matrix, and the water-soluble Polyamide is easily completely coated by polyamide, which results in that during the hydrothermal treatment, the water-soluble polyamide coated by polyamide is difficult to contact water and dissolve in water, making it difficult to form an effective pore structure; in addition, when the water-soluble polyamide and the porous inorganic material are blended in Comparative Example 4, the viscosity of the water-soluble polyamide is already very high and it cannot effectively diffuse into the pore structure of the porous inorganic material. In the subsequent spinning process, the polyamide will enter the pore structure of the porous inorganic material, blocking the pore structure of the porous inorganic material, and cannot be dissolved during the hydrothermal treatment. The above reasons all lead to the fact that the specific surface area of the porous polyamide fiber prepared in Comparative Example 4 does not increase significantly and the weight does not decrease significantly after hydrothermal treatment.
[0184] Comparative Example 5
[0185] A method for preparing porous polyamide fiber is basically the same as Example 7, except that the porogen in this comparative example is the porogen in comparative example 1.
[0186] The spinning cannot be carried out smoothly, and the fiber forming process will cause adhesion, droplets and broken ends.
[0187] Comparative Example 6
[0188] A method for preparing porous polyamide fiber is basically the same as Example 7, except that the porogen in this comparative example is the porogen in comparative example 2.
[0189] The specific surface area of the porous polyamide fiber finally obtained after hot water treatment does not increase significantly compared with that before hot water treatment, and the weight reduction is not obvious.
[0190] Comparative Example 7
[0191] A method for preparing porous polyamide fiber is basically the same as Example 7, except that the porogen in this comparative example is the porogen in comparative example 3.
[0192] The spinning cannot be carried out smoothly, and the fiber forming process will cause adhesion, droplets and broken ends.
[0193] Example 8
[0194] A method for preparing porous polyamide fiber, the specific steps are as follows:
[0195] (1) Raw material preparation:
[0196] Porogen: prepared in Example 2 above;
[0197] Polyamide: fiber grade polyamide 66;
[0198] (2) Preparation of porous polyamide fibers:
[0199] After melt blending and spinning the porogen and polyamide by FDY process to obtain fibers, the fibers are soaked in hot water and post-treated to obtain porous polyamide fibers;
[0200] Among them, the mass of the porogen accounts for 10% of the total mass of the porogen and polyamide, the spinning temperature is 280°C, the spinning speed is 3000m / min, the cooling air temperature is 18°C, the cooling air speed is 0.5m / s, the cooling air relative humidity is 85%, the immersion temperature is 56°C, and the time is 1h; the mass of fiber and hot water is 1:60.
[0201] The final porous polyamide fiber has a single fiber fineness of 2 dtex, a breaking strength of 2.8 cN / dtex, and a breaking elongation of 23%. The average pore size of the porous structure in the porous polyamide fiber is 128 nm, and the specific surface area of the porous polyamide fiber is 15 m 2 / g, the comparative area of the fiber increased by 9 times and the weight decreased by 23% compared with that before hydrothermal treatment.
[0202] Example 9
[0203] A method for preparing porous polyamide fiber, the specific steps are as follows:
[0204] (1) Raw material preparation:
[0205] Porogen: prepared in Example 3 above;
[0206] Polyamide: fiber grade polyamide 6 / 66;
[0207] (2) Preparation of porous polyamide fibers:
[0208] After melt blending and spinning the porogen and polyamide by FDY process to obtain fibers, the fibers are soaked in hot water and post-treated to obtain porous polyamide fibers;
[0209] Among them, the mass of the porogen accounts for 20% of the total mass of the porogen and polyamide, the spinning temperature is 220°C, the spinning speed is 2500m / min, the cooling air temperature is 15°C, the cooling air speed is 0.6m / s, the cooling air relative humidity is 70%, the immersion temperature is 100°C, and the time is 0.8h; the mass of fiber and hot water is 1:50.
[0210] The final porous polyamide fiber has a single fiber fineness of 3 dtex, a breaking strength of 2.5 cN / dtex, and a breaking elongation of 16%. The average pore size of the porous structure in the porous polyamide fiber is 10 nm, and the specific surface area of the porous polyamide fiber is 20 m 2 / g, the comparative area of the fiber increased by 12.5 times and the weight decreased by 30% compared with that before hydrothermal treatment.
[0211] Example 10
[0212] A method for preparing porous polyamide fiber, the specific steps are as follows:
[0213] (1) Raw material preparation:
[0214] Porogen: prepared in Example 4 above;
[0215] Polyamide: fiber grade polyamide 6;
[0216] (2) Preparation of porous polyamide fibers:
[0217] After melt-blending and spinning the porogen and polyamide by UDY process to obtain fibers, the fibers are soaked in hot water and post-treated to obtain porous polyamide fibers;
[0218] Among them, the mass of the porogen accounts for 30% of the total mass of the porogen and polyamide, the spinning temperature is 225°C, the spinning speed is 800m / min, the cooling air temperature is 30°C, the cooling air speed is 0.8m / s, the cooling air relative humidity is 65%, the soaking temperature is 85°C, and the time is 0.5h; the mass of fiber and hot water is 1:45.
[0219] The final porous polyamide fiber has a single fiber fineness of 5.5 dtex, a breaking strength of 1.5 cN / dtex, and a breaking elongation of 50%. The average pore size of the porous structure in the porous polyamide fiber is 120 nm, and the specific surface area of the porous polyamide fiber is 18 m 2 / g, the comparative area of the fiber increased 11 times and the mass decreased 28% compared with that before hydrothermal treatment.
[0220] Embodiment 11
[0221] A method for preparing porous polyamide fiber, the specific steps are as follows:
[0222] (1) Raw material preparation:
[0223] Porogen: prepared in Example 5 above;
[0224] Polyamide: fiber grade polyamide 6;
[0225] (2) Preparation of porous polyamide fibers:
[0226] After melt blending and spinning the porogen and polyamide by POY process to obtain fibers, the fibers are soaked in hot water and post-treated to obtain porous polyamide fibers;
[0227] Among them, the mass of the porogen accounts for 5% of the total mass of the porogen and polyamide, the spinning temperature is 230°C, the spinning speed is 2000m / min, the cooling air temperature is 20°C, the cooling air speed is 0.5m / s, the cooling air relative humidity is 70%, the soaking temperature is 50°C, and the time is 2h; the mass of fiber and hot water is 1:10.
[0228] The final porous polyamide fiber has a single fiber fineness of 3.6 dtex, a breaking strength of 2 cN / dtex, and a breaking elongation of 35%. The average pore size of the porous structure in the porous polyamide fiber is 300 nm, and the specific surface area of the porous polyamide fiber is 2 m 2 / g, the comparative area of the fiber increased by 2 times and the weight decreased by 5% compared with that before hydrothermal treatment.
[0229] Example 12
[0230] A method for preparing porous polyamide fiber, the specific steps are as follows:
[0231] (1) Raw material preparation:
[0232] Porogen: prepared in Example 6 above;
[0233] Polyamide: fiber grade polyamide 6;
[0234] (2) Preparation of porous polyamide fibers:
[0235] After melt blending and spinning the porogen and polyamide by FDY process to obtain fibers, the fibers are soaked in hot water and post-treated to obtain porous polyamide fibers;
[0236] Among them, the mass of the porogen accounts for 10% of the total mass of the porogen and polyamide, the spinning temperature is 260°C, the spinning speed is 3500m / min, the cooling air temperature is 16°C, the cooling air speed is 0.3m / s, the cooling air relative humidity is 70%, the immersion temperature is 66°C, and the time is 1h; the mass of fiber and hot water is 1:40.
[0237] The final porous polyamide fiber has a single fiber fineness of 1.1 dtex, a breaking strength of 3 cN / dtex, and a breaking elongation of 10%. The average pore size of the porous structure in the porous polyamide fiber is 285 nm, and the specific surface area of the porous polyamide fiber is 11 m 2 / g, the comparative area of the fiber increased by 7.3 times and the mass decreased by 10% compared with that before hydrothermal treatment.
Claims
1. A porogen, characterized in that: It includes a porous inorganic material and a water-soluble polyamide coated and filled with the porous inorganic material. The structural formula of the water-soluble polyamide is as follows: ; In the formula, m is an integer in the range of [6, 28], n is an integer in the range of [1, 5], x is an integer in the range of [4, 20], y is an integer in the range of [2, 18], and R is a polyoxyethylene segment or a polyoxypropylene segment.
2. A porogen according to claim 1, characterized in that: The porous inorganic material is a porous carbon material or a porous natural mineral powder, with a particle size of 0.5 to 5 microns and a pore size not exceeding 200 nanometers.
3. A porogen according to claim 1, characterized in that: The relative molecular mass of the porogen is 14000~33000 g / mol, the molecular weight distribution index is 1.5~3.0, the melting point is 170~220°C, the crystallization temperature is 120~180°C, and the solubility of the porogen in hot water at 50~100°C is 10~50 g / 100g.
4. A method for preparing a porogen as claimed in any one of claims 1 to 3, characterized in that: Caprolactam, dibasic acid, amide salt and deionized water are mixed and subjected to a ring-opening reaction to obtain a double-terminal carboxyl polyamide prepolymer, and then a polyether diamine, a reaction aid and a porous inorganic material are added to carry out a condensation reaction to obtain a porogen, wherein the amide salt is obtained by a salt-forming reaction of sodium 5-sulfonate of isophthalic acid and an aliphatic diamine.
5. The method according to claim 4, characterized in that The dibasic acid is one or more dibasic acids of C4 to C20; The relative molecular mass of the double-terminated carboxyl prepolymer is 1500g / mol~5000g / mol; The polyether diamine is one or more of polyoxyethylene diamine and polyoxypropylene diamine; the relative molecular mass of the polyether diamine is 400-4000 g / mol; The reaction aid is a mixture of a catalyst, an antioxidant and a heat stabilizer; The aliphatic diamine is one or more of C4 to C20 diamines.
6. The method according to claim 4, characterized in that The molar ratio of caprolactam to the dibasic acid is 6-28:1, the mass of the amide salt is 50-100% of the mass of caprolactam, the mass of deionized water is 2-3% of the mass of caprolactam, the molar ratio of the polyether diamine to the dibasic acid is 1-1.05:1, the mass of the catalyst is 0.01-1wt% of the total mass of the caprolactam, the dibasic acid, the amide salt and the polyether diamine, the mass of the antioxidant is 100-500ppm of the total mass of the caprolactam, the dibasic acid, the amide salt and the polyether diamine, the mass of the heat stabilizer is 100-500ppm of the total mass of the caprolactam, the dibasic acid, the amide salt and the polyether diamine, and the mass of the porous inorganic material is not less than 5% of the total mass of the caprolactam, the dibasic acid, the amide salt and the polyether diamine.
7. The method according to claim 4, characterized in that The pressure of the ring-opening reaction is 0.01~0.6MPa, the temperature is 210~250℃, and the time is 2~5h; the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction. The pressure of the pre-polycondensation reaction is 0.01~0.3MPa, the temperature is 230~260℃, and the time is 1~3h. The pressure of the final polycondensation reaction is 5~300Pa, the temperature is 250~280℃, and the time is 3~5h.
8. The method according to claim 4, characterized in that The preparation process of the amide salt is as follows: sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water are placed in a salt-forming reactor for reaction until the pH value of the system is in the range of 7.2-7.5, wherein the molar ratio of sodium 5-sulfoisophthalic acid and aliphatic diamine is 1:1.01-1.05, and the amount of deionized water is 50-80wt% based on the total mass of sodium 5-sulfoisophthalic acid, aliphatic diamine and deionized water; the reaction temperature is 50-95°C, the reaction pressure is 0.1-0.2MPa, and the reaction is accompanied by stirring at a stirring speed of 100-200r / min.
9. The use of a porogen according to any one of claims 1 to 3, characterized in that: After the porogen and polyamide are melt-blended and spun to obtain fibers, the fibers are soaked in hot water and post-treated to obtain porous polyamide fibers.
10. The use according to claim 9, characterized in that: The polyamide is fiber grade polyamide 6, fiber grade polyamide 66 or fiber grade polyamide 6 / 66; The mass of the porogen accounts for 5-30% of the total mass of the porogen and the polyamide; Melt blend spinning adopts UDY process, POY process or FDY process; The spinning process parameters of the UDY process include: spinning temperature 220~280℃, spinning speed 500~1500m / min, cooling air temperature 20~30℃, cooling air speed 0.3~1m / s, cooling air relative humidity 60%~80%; The spinning process parameters of the POY process include: spinning temperature 220~280℃, spinning speed 1500~2500m / min, cooling air temperature 15~25℃, cooling air speed 0.3~0.6m / s, cooling air relative humidity 60%~80%; The spinning process parameters of the FDY process include: spinning temperature 220~280℃, spinning speed 2500~3500m / min, cooling air temperature 15~20℃, cooling air speed 0.3~0.6m / s, cooling air relative humidity 70%~85%; The soaking temperature is 50~100℃, the soaking time is 0.5~2h; the mass ratio of fiber to hot water is 1:10~60; The single fiber fineness of porous polyamide fiber is 1.1~5.5dtex, the breaking strength is 1.5~3.0cN / dtex, and the breaking elongation is 10~50%; the pore size of the porous structure in the porous polyamide fiber is 10~300nm; the specific surface area of the porous polyamide fiber is 2~20m 2 / g, the specific surface area of the fiber increases by 2~12.5 times compared with that before hydrothermal treatment, and the weight decreases by 5~30%.
